Defining the optimal design of the inflammatory bowel disease multidisciplinary team: results from a multicentre qualitative expert-based study. Issue 4 (26th March 2015) - Morar, Pritesh; Read, Jamie; Arora, Sonal; Hart, Ailsa; Warusavitarne, Janindra; Green, James; Sevdalis, Nick; Edwards, Cathryn; Faiz, Omar
Abstract : Objective: To elicit expert views to define the aims, optimal design, format and function of an inflammatory bowel disease (IBD) multidisciplinary team (MDT) with the overall purpose of enhancing the quality of MDT-driven care within an IBD service provision. Design: This study was a multicentre, prospective, qualitative study using a standard semistructured interview methodology. Participants: A multidisciplinary sample of 28 semistructured interviews of which there are six consultant colorectal surgeons, six IBD nurse specialists, seven consultant gastroenterologists, five consultant radiologists and four consultant histopathologists. Setting: Participants were recruited from 10 hospitals, which were a mixture of community hospitals and specialist IBD centres between June and October 2013. Results: Experts argued that the main goal of MDT-driven IBD care is to improve patient outcomes via sharing collective expertise in a formalised manner. Themes regarding the necessary requirements for an IBD MDT to occur included good attendance, proactive contribution, a need to define core members and appropriate and functional computer facilities. Emergent themes regarding the logistics of an effective IBD MDT included an eligibility criterion for case selection and discussion and appropriate scheduling. Themes regarding the overall design of the IBD MDT included a 'hub-and-spoke' model versus a 'single-centre' model. Conclusions: Defining key elements for an optimal design format for the IBD MDT is necessary to ensure quality of care and reduce variation in care standards. This study has produced a set of expert-based standards that can be used to structure the IBD MDT. These standards now require larger scale validation and consensus prior to becoming a practical guideline for the management of IBD care.